Review: Neurochemical Aspects of Mental Health and Neurological Diseases - Umaru, Isaac John; Innocent, Nwofor; Umaru, Kerenhappuch Isaac (Darul Yasin Al Sys, 2024)
Neurochemistry is the study of chemicals, including neurotransmitters, hormones, and other molecules, that influence the function and behavior of the nervous system. This field has evolved significantly since the early 20th century, driven by key discoveries and technological advancements such as Neurotransmitters and Mental Health,